Comparison Between Low-Carbon Steel and Galvanized Steel by Deep Drawing Under the Influence of Different Parameters - Abdullah, Mostafa Adel; Abed, Aseel Hamad; Mansor, Khalida Kadhim (Management systems in production engineering, 2025)
Deep drawing is used to make a lot of different shapes. The purpose of this paper is to evaluate the thickness alteration behavior of deep-drawn cylindrical cups with dimensions (41.5 mm) and high (30 mm) under the influence of diverse factors such as the radius of the die’s (R = 9, 6.3 mm), velocity (v = 100, 300, 500 mm/min), thickness (t = 0.7, 0.5 mm), and the kind of metals used (L.c. steel and G. steel). ANSYS Workbench 21.0 software was used to implement the numerical simulation process, followed by constructing a cylindrical cup. The results reveal the highest thinning thickness (10.062% FEA, 15.626% EXP) in the curve area of the cup with low-carbon steel (t = 0.7 mm), while growth in punch speed and a decrease in the radius of the die results in higher thinning. The findings revealed a good agreement between experimental and numerical work, with the highest discrepancy being 5%. The galvanized steel metal demonstrated superiority in the cup’s curve region, where the thinning rate was less than 2.35% compared to the low-carbon steel. Working with smaller radii makes the cup break while working with larger radii makes it wrinkle more. So, intermediate radii, which are four to ten times the width of the piece, need to be worked.